Alexander Balmain papers - Balmain, Alexander, 1740-1821.
Volume consisting of Balmain's accounts while serving as the rector of Frederick Parish, Winchester, Va., following the American Revolution; register of baptisms, marriages, and funerals 1783-1819; lists of subscribers for the support of the parish church; and a list of slaves with birthdates. Also includes correspondence concerning the economic impact of the war on Episcopal ministers in Virginia; Balmain's efforts after the war to collect back pay and title to land due for his service as chaplain with the13th Virginia Regiment of the U.S. Continental Army; the founding of Washington College, Chestertown, Md.; Robert Morris service as U.S. Superintendent of Finance, 1781-1784; and the Asgill Affair, 1782, involving New Jersey Patriot militia commander Joshua Huddy, British Army officer Charles Asgill, and Loyalist Richard Lippincott. Also includes a document recording purchases made by Balmain.
Negative photocopies of originals in private hands.
Private
Clergyman. Rector of Augusta Parish, Va., before the American Revolution, rector of Frederick Parish during the postwar period; and chaplain in the Virginia Line.
Collection material in English.
Keywords: Asgill, Charles, -- Sir, -- 1760?-1823.; Huddy, Joshua, -- -1782.; Morris, Robert, -- 1734-1806.; United States. -- Army -- Pay, allowances, etc; United States. -- Continental Army. -- Virginia Regiment, 13th; United States. -- Office of Finance; Washington College (Chestertown, Md.); American loyalists; Registers of births, etc. -- Virginia -- Winchester; Church records and registers -- Virginia -- Winchester; Episcopal Church -- Virginia; Episcopal Church -- Virginia -- Clergy; Finance, Public -- United States -- History -- To 1789.; Marriage records -- Virginia -- Winchester; Slave records -- Virginia -- Winchester; Universities and colleges -- Maryland -- Chestertown; Winchester (Va.) -- History; United States -- History -- Revolution, 1775-1783.; Virginia -- Church history; Clergy